Prescribing errors in hospital inpatients: a three-centre study of their prevalence, types and causes. Issue 1033 (14th July 2011) - Franklin, Bryony Dean; Reynolds, Matthew; Shebl, Nada Atef; Burnett, Susan; Jacklin, Ann
Abstract : Aim: To compare the prevalence and causes of prescribing errors in newly written medication orders and how quickly they were rectified, in three NHS organisations. Methods: Errors in newly written inpatient and discharge medication orders were recorded in Spring/Summer 2009 by ward pharmacists on medical admissions and surgical wards, as well as the number of erroneous doses administered (or omitted) before errors were corrected. Logistic regression analysis was used to explore the effects of ward (nested within organisation) and clinical specialty, and whether the pharmacist had checked the patient's medication history during data collection. Causes were explored using semistructured interviews with key informants. Results: Overall, 1025 prescribing errors were identified in 974 of 6605 medication orders (14.7%, 95% confidence interval (CI) 13.8% to 15.6%). A mean of 0.9 doses were administered (or omitted) before each error was corrected (range 0–11), with differences between specialties and organisations. The error rate on medical admissions wards (16.3%) was significantly higher than that on surgical wards (12.2%), but this was accounted for by the higher proportion of prescribing being on admission, where omission of patients' usual medication was often identified. There were significant differences among wards (and organisations). Contributing factors included lack of feedback on errors, poor documentation and communication of prescribing decisions, and lack of information about patients' medication histories from primary care. Conclusions: There were variations among wards, organisations and specialties in error rates and how quickly they were rectified. Exploring reasons for differences between organisations may be useful in identifying best practice and potential solutions.